Allosteric Modulators of Serotonin Receptors: A Medicinal Chemistry Survey - Leonardo Brunetti; Fabio Francavilla; Marcello Leopoldo; Enza Lacivita (MDPI AG, 2024)
Serotonin (5-hydroxytryptamine, 5-HT) is a neurotransmitter regulating numerous physiological functions, and its dysregulation is a crucial component of the pathological processes of schizophrenia, depression, migraines, and obesity. 5-HT interacts with 14 different receptors, of which 5-HT1A-1FRs, 5-HT2A-CRs, and 5-HT4-7Rs are G protein-coupled receptors (GPCRs), while 5-HT3R is a ligand-gated ion channel. Over the years, selective orthosteric ligands have been identified for almost all serotonin receptors, yielding several clinically relevant drugs. However, the high degree of homology between 5-HTRs and other GPCRs means that orthosteric ligands can have severe side effects. Thus, there has recently been increased interest in developing safer ligands of GPCRs, which bind to less conserved, more specific sites, distinct from that of the receptor's natural ligand. The present review describes the identification of allosteric ligands of serotonin receptors, which are largely natural compounds (oleamide, cannabidiol, THC, and aporphine alkaloids), complemented by synthetic modulators developed in large part for the 5-HT2C receptor. The latter are positive allosteric modulators sought after for their potential as drugs preferable over the orthosteric agonists as antiobesity agents for their potentially safer profile. When available, details on the interactions between the ligand and allosteric binding site will be provided. An outlook on future research in the field will also be provided.